Students' Interest in Learning English Vocabulary for Engineering by Using YouTube - Suardi Suardi (Universitas Cokroaminoto Palopo, 2021)
YouTube is an application that contains a variety of video content in which there are various kinds of videos, both non-academic and academic. With its ease of use, which only requires web access, YouTube is an application that can be used as a learning medium. Likewise with the level of use among students, it allows YouTube to be a media in learning. In this study, using a qualitative approach through a questionnaire to 14 students of Electronical Engineering at the Akademi Teknologi Industri Dewantara Palopo who were given 20 statements using the Likert Scale, it was found that 11 students (78.57 percent) of the students' high interest, 3 students (21.43 percent) of the students 'very high interest, and none of the students' moderate interest, low interest and very low interest. This shows that student interest in studying on YouTube is very high.